2019
DOI: 10.1007/s40368-019-00501-0
|View full text |Cite
|
Sign up to set email alerts
|

Revitalisation endodontic treatment of traumatised immature teeth: a prospective long-term clinical study

Abstract: Purpose Continuation of root development following revitalisation endodontics (RET) has been shown to be unpredictable with lower success rates in traumatised teeth. This study reports the outcomes for RET in traumatised teeth over a review period of 4 years. Methods A prospective uncontrolled study, where RET was performed on traumatised upper immature anterior teeth with necrotic pulps in 15 children (mean age = 8.3 years), was conducted. Patients were reviewed at 3, 9, 12, 24, and 48 months, where clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…(2019) that agreed with the present study, in which similar clinical and radiographic outcomes of RET using PRP and BLC were reported. Interestingly, most of the studies assessing success of RET in traumatized teeth, mainly using BLC, has shown a tendency to achieve thickening of dentinal walls and apical closure rather than root lengthening in traumatized immature teeth with nonvital pulps over a long period of time (Nazzal et al, 2019). Therefore, long‐term reporting of the results of the present study is planned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) that agreed with the present study, in which similar clinical and radiographic outcomes of RET using PRP and BLC were reported. Interestingly, most of the studies assessing success of RET in traumatized teeth, mainly using BLC, has shown a tendency to achieve thickening of dentinal walls and apical closure rather than root lengthening in traumatized immature teeth with nonvital pulps over a long period of time (Nazzal et al, 2019). Therefore, long‐term reporting of the results of the present study is planned.…”
Section: Discussionmentioning
confidence: 99%
“…2012, Nazzal et al . 2018a, 2019). The use of bi‐antibiotic containing no minocycline (Nazzal et al .…”
Section: Discussionmentioning
confidence: 99%
“…The success of RET has been reported in terms of periapical healing, increase in root thickness and/length, apical foramen closure and tooth survival ( 30 ). In the present study complete resolution (healed) of periapical lesion was noted in 54.5% (6/11) for A-PRF and 60% (6/10) for PRF group; and “healing” was noted in 45.5% (5/11) for A-PRF and 40% (4/10) for PRF as scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be attributed to follow-up period, etiology of non-vitality and the methods used for radiographic measurement ( 19 , 25 , 32 ). Further it is possible that with longer follow-up period the root dimensions would continue to increase ( 14 , 30 ). Although in the present study, the follow-up period was longer for A-PRF than PRF group, but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation